Stalingrad the battle that shattered Hitler's dream of world domination - Matthews, Rupert (Arcturus, 2012)
This outstanding illustrated history looks at the titanic struggle that laid waste the second city of the Soviet Union, the greatest battle the world has ever seen. The bitter Battle of Stalingrad was the turning point of World War II on the Eastern Front. The relentless German advances that had seen the panzers sweep hundreds of miles into Russia was finally brought to a halt by sheer force of numbers. Before Stalingrad the Russians never won, after Stalingrad they could not lose.